Definition of indicators of appropriateness in the management of neovascular age-related macular degeneration: An expert opinion. Issue 4 (July 2020) - Avitabile, Teresio; Boscia, Francesco; Dell'Erba, Alessandro; Introini, Ugo; Lanzetta, Paolo; Locatelli, Paolo; Ricci, Federico; Staurenghi, Giovanni; Varano, Monica; Zotti, Fiorenza
Wet age-related macular degeneration is a chronic condition culminating, in most cases, in blindness. The introduction of anti-angiogenic agents in 2006 has represented a major breakthrough in the treatment of the disease, but timely and effective treatment with regular follow-up and monitoring is mandatory to stabilize and preserve visual acuity. In clinical practice, however, appropriate therapy provision is frequently challenged by economic and organizational issues that result in suboptimal visual outcomes and increased incidence of legal blindness. International Guidelines have defined a diagnostic and therapeutic pathway to ensure the best practice in wet age-related macular degeneration management, but reference parameters to evaluate and compare the performance of Retina Centers are lacking. To address the appropriateness of wet age-related macular degeneration management in Italy, a multidisciplinary panel of ten experts gathered in three meetings. They defined three sets of indicators and relative benchmark values that each Center should comply with to ensure patients optimal care already from the first access: (a) clinical intervention indicators, to determine the possible Center's deviation from the diagnostic and therapeutic pathway; (b) outcome indicator, to evaluate the socioeconomic impact of the healthcare systems' performance; (c) management indicators, to test the size of the gap between the Center's supply and demand. Once the indicators have been analyzed, healthcare systems can plan actions to improve appropriateness and monitor their effects. However, to put this in practice, a concerted effort by all parts involved in healthcare provision is required, together with adequate systems to analyze clinical and administrative documentation.